منهج محمد أبي زهرة في المسائل العقدية: دراسة من خلال تفسيره زهرة التفاسير: Muhammad Abu Zahrah’s Methodology in ‘Aqidah Issue: A Study of His Interpretation in Zahrah al-Tafasir - Hasan, Moh. Abdul Kholiq; Hikmawati, Ari (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
Muhammad Abu Zahrah was a contemporary commentator and reformer from Egypt, committed to improving societal conditions through a correct understanding of ‘aqidah (Islamic faith). This study analyzes Abu Zahrah’s method of addressing ‘aqidah issues, as presented in his interpretation of Zahrah al-Tafasir. The study employed a descriptive-analytical approach to achieving this objective, conducting an in-depth analysis of selected ‘aqidah topics in Zahrah al-Tafasir. The findings reveal that Abu Zahrah utilized a distinctive method in engaging with ‘aqidah issues in his interpretation: i. clarifying the guidance of the Qur’an and mutawatir hadith as the foundation for accepting ‘aqidah; ii. avoiding interpretative debates between theological groups; iii. maintaining independence from any specific theological school; iv. anchoring theological opinions in the guidance of the Qur’an; v. advocating an understanding of ‘aqidah based on the perspective of the Qur’an rather than relying on speculative reasoning or philosophical logic. In general, Abu Zahrah adhered to the views of Ahl al-Sunnah wa al-Jama’ah and was influenced, to some extent, by Ash‘ari thought. Although this influence is not explicitly stated, it is evident in some of his theological stances. His educational background at al-Azhar University likely played a significant role in shaping these views.